Macro-Surface Modifications of Subsonic Flow on Airplane Winglets - Mohd Danial, Bin Ibrahim; Miyanaga, Norifumi; Nabilah, Binti Ibrahim; Muhamad Fadzli, Bin Ashari; Amir Azam, Khan; Siti Zaharah, Binti Ibrahim (2015)
Airplane winglets are used to improve the efficiency and noise or vibrations of fixed-wing aircraft. In this paper, the surface modification involves alteration on surface’s features to improve the performance of a product is being conducted. The surface modification was implemented on winglet surface in order to investigate whether the modified winglets provide better performance or not compared to the conventional wing designs. Two types of models were used which is a rectangular plane and airplane winglet, each with different types of surface modifications. For rectangular plane, four surfaces were introduced which is smooth plane, dimpled plane, riveted plane and extruded rivet plane. As for winglets, three surfaces were used which is the smooth winglet, dimpled winglet and riveted winglet. The parameters used for the simulations were based on the actual cruising flight and zero degree angle of attack. From the results, both show that the surface with rivets is better. The flow trajectories show that the flow velocity across riveted surface modified winglet is 5% higher than the smooth conventional winglet.